Interval Exercise Decreases Inflammatory Markers In Obese Female - Irawan, Muhammad Aufar Adfani; Merawati, Desiana Aufar Adfani; Sugiharto, Sugiharto (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study was experimental research with a pretest-posttest control group design. The interval exercise was performed for 45 minutes on a treadmill. Blood samples were taken 30 minutes before exercise and 10 minutes after exercise. The ELISA method was used to measure the TNF-α level. Statistical analysis used the Independent Samples T-Test and Paired Sample T-Test with a significance level (p<0.05). The results of the Paired Sample T-Test on CO and IE showed that there were no significant difference in the mean of TNF-α levels between pre-exercise and 10 minutes post-exercise (p>0.05). The results of the Independent Samples T-Test showed that there were no significant difference in the mean of TNF-α levels on CO and IE in pre-exercise (p>0.05), while the mean of TNF-α levels in 10 minutes post-exercise between CO vs IE showed a significant difference (p<0.05)